INVESTIGATION OF LEARNING STYLE OF SENIOR HIGH SCHOOL LEARNERS - Suparsih, Imas (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
It is widely believed that understanding learners’ learning is important it can benefit both learners and teachers because every learner has different learning styles in learning. This study is designed to investigate how learners learn and why they have different learning styles. Qualitative approach was chosen to get in-depth explanation about the issues. Semi structure interview was conducted to 2 tenth graders and the data obtained were analyzed descriptively. The finding showed that learning style can be formed by sense experience, environment and learners’ behavior. Further research on investigating of different learning style with more representative sample is recommended.